EFFECTIVENESS OF THE WASTE MANAGEMENT PROGRAMME (TPS3R) IN KALISAMPURNO VILLAGE, TANGGULANGIN SUBDISTRICT, SIDOARJO REGENCY - Afriani, Imama; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Indonesia faces complex challenges in waste management, with the waste management paradigm shifting from an end-of-pipe system to a 3R approach. This study aims to analyse and describe the effectiveness of the waste management programme (TPS3R) in Kalisampurno Village, Tanggulangin Subdistrict, Sidoarjo Regency. Method: This study uses a descriptive qualitative method based on Steers' theory of effectiveness (goal attainment, integration, and adaptation). Data collection techniques include interviews, observations, and documentation with key informants (village head, village secretary, coordinator, administrator, and TPS3R officers) selected through purposive sampling, and data analysis used the Miles and Huberman interactive model. Result: The effectiveness of TPS3R waste management in Kalisampurno Village still needs to be improved, where the aspect of goal achievement shows that it has not been comprehensively achieved, the aspect of institutional integration shows that the management of TPS3R Kalisampurno has fairly good coordination, and the aspect of adaptation shows the inability of the system to adapt to environmental changes. Novelty: This study provides a new contribution by comprehensively applying Steers' effectiveness theory to measure the effectiveness of TPS3R through three dimensions (goal achievement, integration, and adaptation) that have not been widely applied in waste management evaluations.